Uso de blogs na promoção da argumentação no ensino médio de Química - Dias, Fabiane Elidia (2020)
In chemistry education, blogs have been used as a pedagogical strategy, enabling students to participate more actively in the teaching and learning process. This research aims to develop and stimulate argumentative practice in high school chemistry classes based on blogs and looking for answers to the following research question: to what extent did the strategy of using blogs help students develop arguments and what can be said about the structural quality of those arguments? In this perspective, four groups of students received instructions to create blogs on the socio-scientific topic of pesticide use. In all the blogs, arguments were verified that present data, justifications and conclusions, which are essential elements, according to the Toulmin Model. Furthermore, in all the analyzed arguments, there is more than one justification that, in most cases, is accompanied by a backing, indicating their good structural quality. Considering the nature of the arguments found in the blogs, the approach to questions about health, environment, economy and social aspects is highlighted. Therefore, setting up the blogs gave the students the opportunity to discuss socio-scientific issues, as well as argumentation based on posting comments.